Performance and Energy Saving Analysis of Grid Connected Photovoltaic in West Sumatera - Syafii Ghazali; Refdinal Nazir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The paper presents performance and energy saving analysis of 1.25 kWp grid connected Photovoltaic system under difference weather condition in West Sumatera.  The measured data were performed during weather data that often occur in West Sumatra i.e. sunny, overcast, raining and cloudy. The synchronizing process successfully done even bad weather conditions when sunlight was low automatically. Photovoltaic in average start producing power from 7:00 AM to 6:00 PM for normal or clear sky, however under overcast, raining and cloudy weather, the PV power decreased and disconnected earlier before sunset. During intermittent raining, overcast and cloud covered the PV power output show an irregular profile. The PV energy saving performed for three residential connection cases: 1300 VA, 900 VA with subsidized and 900 VA without subsidized. The solar PV installation have more benefits and energy saving for 1300 VA, 900 VA without subsidized with payback period around 8.5 years. However, the 900 VA with subsidized take longer 20.8 years, but still in PV lifespan 25 years. In the future, household subsidies may be reduced or eliminated, the solar energy will be viable alternative of energy resources when it can produce electricity at a cost equivalent to utility grid PLN rate.